Tigawasa Buleleng Tourism Village Development - Tri Sutaguna, I Nyoman (Journal of Management, 2023)
Since Tigawasa Village issued Perdes No.65 of 2020 to conserve the declining bird population, residents who work as bird attractors have been concerned that their jobs may be destroyed. The goal of this research is to explain how birds and humans may cohabit with reciprocal advantages, as demonstrated by sustainability and ecotourism campaigners in Tigawasa Village, Buleleng, Bali. The descriptive qualitative method was used in this study, with data collected through a literature review. The involvement of people who already understand the value of sustainability, in this example, Bamboo Plaiting, is critical to the success of ecotourism management in Tigawasa Village.